FUNDAMENTAL AND TECHNICAL ANALYSIS AS THE BASIS FOR SHARE INVESTMENT DECISION MAKING - Putri, Mahrani; Aminda, Renea Shinta; Yudhawati, Diah (Manager : Jurnal Ilmu Manajemen, 2023)
At the beginning of 2020, when the COVID-19 virus entered Indonesia, the Indonesian economy slumped and experienced a decline. However, there are some companies that actually benefit and the fluctuations in the company's stock price tend to be stable. One of them is a pharmaceutical company. Over time, when the Indonesian people began to adapt, many industrial companies were targeting investors from the community to be used as a source of capital for their companies through the capital market. Before investing in stocks, investors should first examine their stocks with fundamental and technical analysis. The purpose of this research is for investment decisions to sell and buy stocks with fundamental and technical analysis. This research is quantitative descriptive. The population of this study is the pharmaceutical sub-sector companies listed on ISSI for the period 2019-2021. The decision-making method in this study uses purposive sampling and the number of samples is 8 companies. This study uses secondary data and research variables, namely NPM, ROA, ROE, PBV and RSI. The results obtained in this study, with a fundamental analysis of the financial performance of 8 pharmaceutical sector companies, 5 companies including PT. Darya Varia Laboratoria Tbk, PT. Kalbe Farma Tbk, PT. Merck Indonesia Tbk, PT. Industri Jamu dan Farmasi Sido Muncul Tbk, dan PT. Tempo Scan Pasific Tbk. have good financial performance. And 3 companies, namely PT. Indofarma Tbk, PT. Kimia Farma, PT Pharos Tbk experienced a decline. The best year's PBV for stock transactions is in 2021 with an average of 4.23. With the Technical Analysis of the Relative Strength Index, in 2019 PT. Industri Jamu dan Farmasi Sido Muncul Tbk, PT. Darya Varia Laboratoria Tbk received the highest return. In 2020, PT Indofarma Tbk and PT Kimia Farma Tbk received the highest returns. Then in 2021 PT. Industri Jamu dan Farmasi Sido Muncul Tbk, PT. Darya Varia Laboratoria Tbk and PT Indofarma Tbk produced the highest returns.”